ANALISIS KOMPONEN GIZI DAN KANDUNGAN BAHAN BERBAHAYA BAKSO DAGING SAPI YANG DIPASARKAN DI KOTA DENPASAR - Mulyani, Sri; Wrasiati, Luh Putu; -, Fakhrudin (Agrotekno; Vol. 12, No. 1 Februari 2006)
The aims of the research were to find out the content of nutrition, and to detect the borax and formalin on beef meat balls (bakso sapi) sold in Denpasar. Samples taken from five brands of bakso sold in 8 supermarkets. Analysis was undertaken for the content of ash, fat, water and protein, and also a qualitative analysis to detect borax and formalin. The results showed that many samples did not fulfill the standards (SNI) particularly on fat and water content. None of the samples contained borax, but samples from two brands contained of formalin.
Keywords: Bakso, formalin, boraks